DATA SECURITY DESIGN HEALTH SYSTEM USING cryptographic SmartCard - Yudi Irawan Chandra (STMIK Jakarta, 2003)
Person's medical record information is one factor that determines the quality of serviceprovided by central health care services to patients and, therefore, this medical recordinformation should always be there when needed. Confidentiality of medical recordinformation is very important because this information to explain the special relationshipbetween patient and physician, which must be protected from leakage according to the codeof medical ethics and the applicable legislation.Smart card technology (smartcard) offers convenience and security of data storage because ofthe mechanism for data encryption before the data is stored in memory, and the pin (secretcode) that maintain such data in order not to be read by unauthorized parties. Smartcard canalso be easily carried so as to ensure the availability of data whenever needed.